Modeling riverine dissolved and particulate organic carbon fluxes from two small watersheds in the northeastern United States. (February 2020) - Qi, Junyu; Du, Xinzhong; Zhang, Xuesong; Lee, Sangchul; Wu, Yiping; Deng, Jia; Moglen, Glenn E.; Sadeghi, Ali M.; McCarty, Gregory W.
Abstract: The coupled carbon (C) cycle across terrestrial and aquatic environments at the watershed scale has been identified as an important, but poorly constrained component of the global carbon budget. Here, we extended Soil and Water Assessment Tool (SWAT) with coupled riverine particulate organic carbon (POC) and dissolved organic carbon (DOC) modules (referred to as SWAT-C hereafter). Results show that SWAT-C reproduced daily POC and DOC fluxes well in two watersheds in the Northeastern United States. We found that SWAT-C tended to underestimate high flows and peak DOC and POC fluxes. Uncertainty analysis indicated flux uncertainties associated with POC and DOC simulations were larger than those for flow simulation. Sensitive parameters controlling POC and DOC biogeochemical processes were identified along with how these parameters influence mechanisms underlying C cycling. We anticipate that the tool developed and applied here will inform C related ecosystem services in watershed assessment and planning. Highlights: We added new processes into the SWAT model for riverine POC and DOC modeling. The SWAT-C model performed well for simulating daily POC and DOC fluxes in two watersheds. Uncertainty and sensitivity analyses were performed to understand key parameters controlling riverine carbon fluxes. We anticipate the new capabilities of SWAT-C help inform watershed scale carbon management.